AFFERENT PATHWAYS INVOLVED IN CARDIOVASCULAR ADJUSTMENTS INDUCED BY HYPERTONIC SALINE RESUSCITATION IN RATS SUBMITTED TO HEMORRHAGIC SHOCK - Eloísa Ferreira de Almeida Costa; Gustavo Rodrigues Pedrino; Oswaldo Ubrı́aco Lopes; Sérgio L. Cravo (2009)
The peripheral hyperosmolarity elicited by intravenous infusion of hypertonic saline (HS) can be beneficial in treating hemorrhagic shock. However, the neural mechanisms involved in this resuscitation remain unknown. The present study sought to determine the effects of selective baroreceptor denervation on arterial blood pressure response during HS resuscitation in rats submitted to hemorrhagic shock. Male Wistar rats (280-320 g) were anesthetized with thiopental sodium (40 mg/kg, i.v.), and the femoral artery and jugular vein were cannulated for MAP and heart rate recording and HS infusion (3 mol/L NaCl; 0.18 mL/100 g body weight, >2 min). Hemorrhagic shock was obtained by withdrawing blood over 30 min until a MAP of 60 mmHg was obtained. This level of MAP was maintained for a further 30 min through subsequent blood withdrawal or reinfusion. Next, animals were divided into selective aortic and/or carotid denervation or sham groups before infusing HS. Results showed that in the sham group (n = 12), HS infusion increased MAP to levels close to baseline (from 65 +/- 3 to 112 +/- 5 mmHg, 10 min after HS). In the aortic denervated group (n = 10), HS infusion also increased MAP (from 54 +/- 3 to 112 +/- 5 mmHg, 10 min after HS). In contrast, in the carotid denervation group (n = 8), the increase in MAP induced by HS infusion was abolished (from 53 +/- 3 to 73 +/- 12 mmHg, 10 min after HS). These results indicate that in hemorrhaged rats, HS infusion produces a pressor effect that is likely to be mediated through carotid rather than aortic baroreceptors.